Institute of Socio-Political Research of the Russian Academy of Sciences - S. V. Rogachev (Vestnik MGIMO-Universiteta)
Abstract: Review of the book by Milovidov V. D. Simmetry of delusions. Uncertainty factors of the global financial market under the technological revolution. Moscow, Magistr, 2019. 336 p. (In Russian).Author declares the absence of conflict of interests.